Hepatitis Delta Virus Diagnosis - Olivero, Antonella; Smedile, Antonina (Seminars in Liver Disease, 2012)
The first step in the diagnosis of hepatitis delta virus (HDV) infection is testing HBsAg-positive individuals for the antibody to the HD antigen (anti-HD).In anti-HD-positive patients, the next step is testing for HDV RNA in serum to determine whether the antibody reflects an ongoing active HDV infection (HDV-RNA-positive) or represents a serologic scar to past HDV infection (HDV-RNA-negative). In the HDV-positive individual with liver disease, it is critical to distinguish acute HDV/hepatitis B virus (HBV) coinfection from chronic HDV superinfection in HBsAg carriers; the course, prognosis, and management of the two conditions are different. The differential diagnosis can be achieved through the scrutiny of the battery of HDV and HBV markers, which combine in patterns characteristic for each condition.Standardized competitive and μ-capture commercial assays are available to determine the IgG and IgM antibody to HDV. Several in-house assays were developed to determine HDV RNA in serum; the sensitivity threshold of current polymerase chain reaction-based assays is 10 copies of HDV RNA/mL. Unfortunately, HDV-RNA assays are not yet standardized and the results from different laboratories often are not comparable due to different sensitivities. The development of an international reference HDV-RNA standard remains an unmet diagnostic need.
Keywords: HDV; HDV-RNA; anti-HD IgG; anti-HDIgM; RT-PCR; CHD